O pioneers - Cather, Willa 1873-1947 (Houghton Mifflin, 1941)
The story of the Bergson family and their friends and neighbors. Describes the pioneers' struggle for survival in the barren, underdeveloped Nebraska tableland.
Keywords: Frontier and pioneer life -- Nebraska -- Fiction; Nebraska -- Fiction; Aufsatzsammlung; Fiktionale Darstellung; Quelle